The role of presynaptic dopaminergic imaging in acquired neurological conditions affecting basal ganglia: a systematic review - Ardila Jurado, Elena; Zünd-Hofer, Lisa; Brugger, Florian; Nicastro, Nicolas; Bhatia, Kailash P.; Kägi, Georg (Frontiers in Neurology, 2025)
BackgroundDopaminergic imaging has become a pivotal tool in the diagnosis of Parkinson's disease (PD) and related disorders. Its ability to assess presynaptic dopamine transporter function provides crucial insights for distinguishing PD from other acquired neurological disorders. Recent advances have also demonstrated its utility in evaluating diseases beyond PD, including non-degenerative conditions associated with parkinsonism.ObjectivesThis review aims to explore the diagnostic and therapeutic value of dopaminergic imaging across a range of acquired disorders, including normal pressure hydrocephalus, Holmes tremor, vascular parkinsonism, infectious and metabolic diseases as well as autoimmune encephalopathies with a particular focus on its clinical implications, imaging patterns and predictive value for treatment response. We excluded drug induced conditions as they have been extensively reviewed previously.MethodsA comprehensive systematic literature search focusing on studies that utilized dopaminergic imaging techniques was conducted in PubMed. We used the terms “DaTScan.” “Dopaminergic imaging,” “dopamine transporter,” “Single-photon emission computed tomography,” “FP CIT 123 SPECT,” “123I-ioflupane,” “TRODAT” and “18F-DOPA” and focused on acquired neurological disorders. Diagnostic accuracy and imaging patterns across these conditions were analyzed.ResultsDopaminergic imaging revealed variable deficits across acquired disorders, with distinct patterns aiding in the differential diagnosis. In normal pressure hydrocephalus, imaging often shows a reduction in striatal dopamine transporter binding which was reversed post-shunt surgery, distinguishing it from neurodegenerative parkinsonisms. In Holmes tremor, significant presynaptic dopaminergic deficits were associated with levodopa responsiveness. Vascular parkinsonism exhibited more diffuse and symmetric dopamine transporter reductions compared to idiopathic PD, correlating with poorer levodopa response.ConclusionDopaminergic imaging plays a crucial role in differentiating PD from acquired diseases presenting with parkinsonism. Its diagnostic utility, combined with clinical and pathological findings, enhances therapeutic decision-making, particularly in more common conditions like normal pressure hydrocephalus, Holmes tremor and vascular parkinsonism. As imaging techniques continue to evolve, their integration into clinical practice will further support personalized treatment strategies.